118 Hospital specialist palliative care and cardiology collaboration – 'a breath of fresh air'. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Banting, Mark; Rose, Hannah
Abstract : Introduction: Symptom burden, including breathlessness, in patients with advanced heart failure is very severe. How best to address these needs in a hospital population is not yet fully addressed. We describe a novel approach to proactive palliative care in this population. Method: University Hospital Southampton has appointed a palliative care consultant with a third of his time dedicated to work proactively with the inpatient heart failure team. In the first year of the post, we have conducted a survey of the heart failure team to ascertain their confidence in management of breathlessness in advanced heart failure. Results: At the time of writing, we had 16 responses (6 consultant, 4 registrar and 6 clinical nurse specialist). NYHA classification was universally used for breathlessness measurement. 45% had no non-pharmacological methods for management with 50% suggesting a fan and far fewer any other methods. Oral and intravenous diuretics were widely used whilst only one said they would use subcutaneous diuretic. 70% use opioids and 45% benzodiazepines. Very few (12.5%) felt confident in management with the majority feeling 'somewhat confident' (50%) or 'not so confident' (37.5%). In answer to the question 'when would you consider referral to palliative care and how would you do this?' the answers ranged from 'don't know' to naming the specific palliative care consultant. The main themes centred on end of life care and symptoms beyond the managing team's confidence. Conclusion and further work The cardiology team demonstrates confidence in managing breathlessness in the modalities they are used to (oral or IV diuretics) but appear to lack confidence in alternative routes or non-pharmacological methods. We will take the results of this survey to proactively target teaching to the cardiology teams, to increase their confidence in breathlessness management but also to raise the profile of palliative care within this patient population.